1991
DOI: 10.1002/1097-0142(19910801)68:3<568::aid-cncr2820680321>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of glial fibrillary acidic protein staining in medulloblastoma

Abstract: Histologic and immunohistochemical properties of 53 medulloblastomas were analyzed with regard to clinical features and survival rate. No correlation was found between survival rate and histologic features of the tumor, such as desmoplastic reaction, number of mitoses, hemorrhages, necrosis, endothelial proliferation, glomerular arrangement, calcifications, rosettes, or oligodendroglial cells. However 82% of the patients with positive glial fibrillary acidic protein (GFAP) staining in numerous tumor cells surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…Most immunohistochemical studies have shown that expression of neuronal proteins, such as synaptophysin or neurofilament protein, does not influence outcome [45,100,135,218]. Other reports have confusingly suggested that the presence of GFAP‐positive tumour cells bestows adverse [100], beneficial [79], or non‐existent effects on the behaviour of MBs [45,197]. The caveat probably applying to any of these findings is that, whatever morphological or immunohistochemical signs of differentiation are exhibited by a MB (or PNET), its biology will ultimately be dictated by the nature of small undifferentiated cells with a high growth fraction.…”
Section: Prognostic Indicators In Medulloblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…Most immunohistochemical studies have shown that expression of neuronal proteins, such as synaptophysin or neurofilament protein, does not influence outcome [45,100,135,218]. Other reports have confusingly suggested that the presence of GFAP‐positive tumour cells bestows adverse [100], beneficial [79], or non‐existent effects on the behaviour of MBs [45,197]. The caveat probably applying to any of these findings is that, whatever morphological or immunohistochemical signs of differentiation are exhibited by a MB (or PNET), its biology will ultimately be dictated by the nature of small undifferentiated cells with a high growth fraction.…”
Section: Prognostic Indicators In Medulloblastomamentioning
confidence: 99%
“…Studies attempting to relate cell proliferation to prognosis in MBs have used a variety of methods for estimating tumour growth. However, whether derived from an index of mitotic activity or a Ki‐67 LI [71,74,79,97,138,146,218], resulting data have been conflicting, many studies showing no relationship with outcome [74,79,97,138,218].…”
Section: Prognostic Indicators In Medulloblastomamentioning
confidence: 99%
“…The current case showed evidence of focal glial differentiation, a finding presumed to impart a worse prognosis [29]. The prognostic value of GFAP expression in medulloblastomas is controversial with discrepant findings reporting either a negative [30] or a positive prognostic impact [31]. GFAP expression has also been attributed merely to entrapped astrocytes [32].…”
Section: Discussionmentioning
confidence: 64%
“…Another histopathological prognostic parameter in MBs, which has received considerable attention but little agreement, is differentiation along glial or neuronal cell lines. [46] Positivity for GFAP have been variably correlated with better prognosis [47,48] by some, while others found it to be either associated with poor prognosis, [49,50] or without any correlation with survival time. [51,52]…”
Section: Cell Differentiationmentioning
confidence: 99%